Effect of social media platforms on consumer online purchase intention: A study of consumers of online products in South East, Nigeria (UNIZIK Journal of Marketing, 2024)
This research investigated the effect of social media platforms on consumer online purchase intention in South East Nigeria. A descriptive survey research design was adopted for the study. Three hundred and fifty (350) respondents, which formed the sample size of the study, were determined using Topman’s formula, and copies of a validated and reliable research instrument were administered to the respondents. The stated hypotheses were tested at a 5% level of significance using multiple regression analysis with the aid of the Statistical Package for Social Sciences (SPSS) version 23.0. The study found that Facebook, Instagram, and TikTok have a significant influence on consumer online purchase intention in South East Nigeria. However, the study revealed that (Twitter) X and YouTube do not have any significant effect on consumer online purchase intention in this region. The study recommends that businesses should invest in targeted advertising on Facebook, Instagram, and TikTok to capitalize on their proven influence on consumer purchase intentions. It further recommends that businesses should better understand the potential efficacy of (Twitter) X and YouTube, as these platforms convey messages about products and services at a glance and possess the capacity to enhance consumer online purchase intention in South East Nigeria.
Keywords: Social media platforms; Facebook; Instagram; TikTok; YouTube; consumer online purchase